Role of cerebrospinal fluid adenosine deaminase activity in the diagnosis of tuberculous meningitis in children - Bindu, T. Hima; Reddy, R. Maheshwara (International Journal of Contemporary Pediatrics, 2017)
Background: Early and correct treatment is essential for successful outcome in patients of tuberculous men-ingitis. Adenosine deaminase activity in the cerebrospinal fluid has been found to be a simple and useful investigation in the diagnosis of tuberculous meningitis in children. Methods: It is a cross sectional observational hospital based study conducted at the Department of Paediatrics, Deccan College of Medical Sciences, Kanchanbagh, Hyderabad, India. Children aged 2 months to 12 years were included in the study during April 2016 to October 2016. Results: The mean value of adenosine deaminase activity in the cerebrospinal fluid of tuberculous meningitis cases was 13.3±14.49. The mean cerebrospinal fluid adenosine deaminase levels in tuberculous meningitis patients was significantly higher than non-tuberculous meningitis patients with P <0.01. Conclusions: The mean cerebrospinal fluid adenosine deaminase level was significantly raised in tuberculous meningitis patients.